The Effect of Single Leg Bound and Split Jump Training on The Straight Kicking Ability of Athletes Dikapasita - Dwinda Rusdiana; Andi Rahman; Siti Ayu Risma Putri; Muhsana El Cintami Lanos (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Low ability of straight kick to Dikapasita martial arts athletes in Teluk Jaya while competing is one of the problems that are emphasized in this study. This study aims to determine the influence of single leg bound and split jump training on Dikapasita straight kick martial artist. This research type is experimental research with an experimental training control design design using a pretest-posttest two group design method. The research subjects were 20 Dikapasita male martial artists in the teenager age category divided into two treatment groups. Data collection techniques use a test and measurement by a straight kick trial test that is carried out before and after providing treatment as well as posttest. The data analysis technique uses descriptive statistics to find out the mean value as well as inferential statistics in the form of t-test at a significance level α= 0.05. The results showed that the average leg straight kick ability in single leg bound training group increased from 17 to 26, whereas the split jump training group increased from 18 to 26. The t-test results show a significant increase in both groups, namely the single leg bound group with t count 25.735 > t table 1.761 and the split jump group with t count 14.720 > t table 1.761. From the results of the study, it can be concluded that single leg bound and split jump training have a significant effect on increasing the ability of Strainght kick martial artists Dikapasita, but single leg bound training is more effective than split jump training.